ANALISIS KERAWANAN DAN KERENTANAN BENCANA GEMPABUMI DAN TSUNAMI UNTUK PERENCANAAN WILAYAH DI KABUPATEN MALUKU TENGGARA BARAT - Prawiradisastra, Suryana (Jurnal Sains dan Teknologi Indonesia, 2011)
The District of Maluku Tenggara Barat is situated between: 07º 06’ 13” - 08º 02’ 08” South Latitudes and 131º 03’ 39” - 131º 45’ 09” East Longitudes. The Broad of Territory in the District of Maluku Tenggara ± 325,725 Ha. Maluku Tenggara Barat District was above three tectonic plates, resulting in the formation of the complex geological conditions, therefore the region include earthquake and tsunami prone area. About 30 percent of the tsunami in Indonesia occurred in the Maluku Sea and Banda Sea. Based on record have occurred BMKG station, 31 tsunami events occurred which caused a big earthquake. Looking at a fairly high frequency, it is important to assess potential earthquake and tsunami disaster in the future. The results of the study the potential for disaster if it is associated with population density, infrastructure and land use will be obtained a vulnerability. Vulnerability is needed in preparing the Regional Development.